Gambaran Dukungan Sosial pada Mahasiswa Psikologi UMSIDA yang Mengerjakan Skripsi - Pananto, Halim; Paryonti, Ramon Ananda (Indonesian Journal Publisher, 2024)
Student is an individual who is in the process of studying a particular discipline. One of the biggest challenges when someone becomes a student is working on a thesis as one of the final forms of the study program being undertaken. Many factors influence how quickly and persistently a person completes it, one of which is social support. This study aims to factually describe how the level of social support is for psychology students who are working on their thesis. This study used quantitative research methods, then used a descriptive approach. The sample of this study was 149 students from a total of 254 student population. The measuring instrument used in this study is the social support scale which is compiled based on 4 aspects of social support and has been tested valid and reliable to use. After the data has been collected and processed, it can be concluded that informative with total of 35% percentage and instrumental support with 41% total of percentage is the highest type of social support obtained by the sample, while emotional support and appreciation support obtained by the research sample is still low with each percentage 34% and 35%.